Wergiliuszowy epyllion o Orfeuszu i Eurydyce: na warsztacie badaczy, artystów, tłumaczy… Transpozycja opowieści do polszczyzny - Arndt, Aleksandra (Collectanea Philologica, 2020)
The article discusses differences in the treatment of the Virgilian epyllion by scholars and artists. It also indicates that the work of a translator is the result of the activities in both areas. A few introductory remarks are followed by Polish translation of the story.